Analysis of Factors Affecting Profitability (Study on Islamic Commercial Banks Registered with the Financial Services Authority in 2018 - 2022) - Nur Fadhilah, Hilya Nisa; Nuryaman, Nuryaman (Dinasti Publisher, 2024)
This study aims to examine the effect of NPF, FDR, and GCG on the profitability of Islamic commercial banks. The data used is secondary data in the form of annual financial reports from 17 Islamic Commercial Banks in Indonesia registered with the Financial Services Authority for the period 2018-2022 so 69 observation data were obtained. The independent variables used are NPF, FDR, and GCG which are proxied by the number of boards of directors and the frequency of board meetings. At the same time, the dependent variable used is return on assets (ROA). The results of this study indicate that FDR has an effect on the profitability of Islamic commercial banks, while NPF, the board of directors, and the board of commissioners have no significant effect on the profitability of Islamic commercial banks.